Semiquantitative evaluation of lymph-vascular space invasion in patients affected by endometrial cancer: Prognostic and clinical implications. (January 2021) - Restaino, Stefano; Tortorella, Lucia; Dinoi, Giorgia; Zannoni, Gian-Franco; Baroni, Alessandro; Capasso, Ilaria; Distefano, Ettore; Sozzi, Giulio; Chiantera, Vito; Scambia, Giovanni; Fanfani, Francesco
Abstract: Objectives: The interpretation of lymph-vascular space invasion (LVSI) is usually qualitative, as presence or absence. The aim of this study is to investigate the prognostic role of LVSI in patients affected by endometrial cancer, when evaluated with a semiquantitative analysis. Methods: This retrospective multicentre study enrolled patients who received a histologically confirmed diagnosis of endometrial cancer. The assessment of LVSI was semiquantitative in accordance with the three-tiered scoring system (absent, focal and diffuse). Results: Among 1258 patients with surgical-stage endometrial cancer, LVSI has been found in 32.8% of cases (n = 412), whose 12.7% (n = 160) were focal, and 20% (n = 252) diffuse. The rate of lymph node metastasis increased from the 5% in patients with no LVSI to 15% in patients with focal LVSI and 33% in those with diffuse LVSI (p < 0.001). Distant recurrences were more frequent in patients with diffuse LVSI than in focal or no LVSI (24.9% versus 14.7% and 6.6%, respectively, p < 0.001). Diffuse LVSI was found to significantly increase the risk of distant metastasis (adjusted odds ratio (A OR) 2.57, p < 0.001). Adjuvant radiation were associated with improved overall survival (OS) and disease-free survival (DFS) in patients with diffuse LVSI. Conclusion: The presence of diffuse LVSI is an independent risk factor for both lymph node metastasis and distant recurrence in endometrial cancer patients, and it is associated with a significantly decreased OS and DFS. Adjuvant radiation improved survival regardless of grading, histotype and lymph nodal metastasis in women with diffuse LVSI. Highlights: Semiquantitative three-tiered classification improves risk stratification. Diffuse lymph-vascular space invasion (LVSI) is an independent risk factor for lymph node metastasis and distant recurrence. Adjuvant radiation improved survival in women with diffuse LVSI.